The Relationship between Cognitive Performance and Pain in Elderly Caregivers - Andrade, Giselle Nascimento de (2020)
Objective: to evaluate the cognitive performance of caregivers of elderly people with pain. Method: This is an exploratory, non-experimental study with a quantitative approach with a cross-sectional design and a non-probabilistic sample of 30 elderly caregivers. Data collection was performed in the waiting room for consultations at the Health Care Center for the Elderly and their Caregivers, Niterói-RJ. Instruments for data collection were used, such as a sociodemographic questionnaire to characterize the sample, the Multidimensional Pain Assessment Scale and the Addenbrooke Cognitive Exam - Revised. Results: female predominance, age between 58 and 65 years, children, who perform comprehensive care. Pain classified as moderate, chronic and persistent in cervical and lumbar regions. Among the cognitive domains, memory had a lower average and there was statistical significance when related to the location of pain with the cognitive examination score. Conclusion: Knowing the socio-demographic and health profile, in addition to assessing pain and cognitive performance, the results of this research can contribute to the scientific basis, development and improvement of health promotion actions, disease prevention and health education as strategies aimed at to the main needs of elderly caregivers.